PENGEMBANGAN MEDIA DONAT (DOMINO MATEMATIKA) BERBASIS GAME BASED LEARNING PADA PEMBELAJARAN MATEMATIKA KELAS V SD NEGERI 49 LUBUK LINGGAU - Putri Permata Sari, Natalia; Rijal, Akmal; Dwi Andita, Cahyo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to develop a Donut media design based on Game Based Learning in Mathematics learning. Testing the validity, practicality, and effectiveness of Game Based Learning-based Donut media in Mathematics learning in grade V students of SD Negeri 49 Lubuk Linggau. This type of research is Research and Development with the ADDIE development model. The subject of this study is a grade V student of SD Negeri 49 Lubuk Linggau. Data collection techniques use observation, interviews, questionnaires, and tests. Based on the results of the analysis of the validity of Game Based Learning-based Donut media in Mathematics learning using Aiken's V, it showed the assessment of the language validator of 0.97, the media validator 0.84, and the material validator 0.94. The analysis of the assessment of teacher and student practicality sheets obtained that the Game Based Learning-based Donut media in Mathematics learning met the criteria of being very practical with an average score of 86.4%. Then the analysis of the effectiveness assessment obtained an average N-Gain score of 0.67 with the medium category. Based on the results of the study, it can be concluded that Donut media based on Game Based Learning in Mathematics learning is proven to be valid, practical, and effective so that it is suitable for use in the learning process of grade V of SD Negeri 49 Lubuk Linggau.